Pimachihowan - MacDonald, Michael B.; Lertzman, David (My University, 2015)
The product of three years of work in Northern Alberta that explores the traditional Cree philosophy of Pimachihowan that roughly translates into living with the land. The northern Cree are First Nations (Indigenous Canadians) living in the Boreal forest, second in size and ecological importance only to the Amazonian Rainforest, an indispensable resource to maintaining life. A Michael MacDonald film; written and produced by Dr. David Lertzman; director, editor, sound: Michael MacDonald; featuring Dr. David Lertzman, Conroy Sewepagaham, and Willard Tallcree; 33:03 minutes. Retrieved from: http://www.michaelbmacdonaldfilms.ca/
Keywords: boreal forest; Cree